Clinical testing for neutralizing antibodies to interferon-β in multiple sclerosis - Creeke, Paul I. (SAGE Publications, 2013)
Biopharmaceuticals are drugs which are based on naturally occurring proteins (antibodies, receptors, cytokines, enzymes, toxins), nucleic acids (DNA, RNA) or attenuated microorganisms. Immunogenicity of these agents has been commonly described and refers to a specific antidrug antibody response. Such immunogenicity represents a major factor impairing the efficacy of biopharmaceuticals due to biopharmaceutical neutralization. Indeed, clinical experience has shown that induction of antidrug antibodies is associated with a loss of response to biopharmaceuticals and also with hypersensitivity reactions. The first disease-specific agent licensed to treat multiple sclerosis (MS) was interferon-β (IFNβ). In its various preparations, it remains the most commonly used first-line agent. The occurrence of antidrug antibodies has been extensively researched in MS, particularly in relation to IFNβ. However, much controversy remains regarding the significance of these antibodies and incorporation of testing into clinical practice. Between 2% and 45% of people treated with IFNβ will develop neutralizing antibodies, and this is dependent on the specific drug and dosing regimen. The aim of this review is to discuss the use of IFNβ in MS, the biological and clinical relevance of anti-IFNβ antibodies (binding and neutralizing antibodies), the incorporation of testing in clinical practice and ongoing research in the field.